Eligibility to Use the Fund's Facilities for Concessional Financing. (Policy Papers; Policy Paper ;, 2012)
This paper proposes to maintain the Poverty Reduction and Growth Trust (PRGT)-eligibility criteria established in early 2010 and considers, based on the application of such criteria, whether updates to the eligibility list are warranted at this time. The premise remains that access to the Fund's scarce concessional resources should be preserved for members with low income and related vulnerabilities, while keeping PRGT eligibility closely aligned with International Development Association (IDA) practices. Based on the application of the PRGT-eligibility framework, no countries are proposed for entry or graduation at this time.